P086 OVER 30% OF SYMPTOMATIC FLARES IN INFLAMMATORY BOWEL DISEASE PATIENTS ARE ASSOCIATED WITH DETECTABLE GASTROINTESTINAL INFECTIOUS AGENTS BY THE BIOFIRE GI PCR PANEL STOOL TEST. (18th January 2018) - Limsrivilai, Julajak; Saleh, Zachary; Johnson, Laura; Stidham, Ryan; Waljee, Akbar; Gutermuth, Brian; Govani, Shail; Brown, Alexandra; Briggs, Emily; Rao, Krishna; Higgins, Peter
Abstract: Background/Aims: GI infections (e.g. C. difficile and CMV) have been shown to worsen inflammatory bowel disease (IBD) activity and result in increased surgeries and hospitalizations. By conventional methods, only 10% of symptomatic IBD patients have detectable concurrent GI infections. Using the BioFire FilmArray GI PCR panel, a stool test capable of detecting 22 enteropathogenic organisms, we investigated the prevalence of GI infections in symptomatic flares of IBD vs. inactive IBD, IBS, and healthy controls and aimed to determine the prevalence and impact of detected infectious agents. Methods: Patient cohorts were: #1: Active Crohn's disease (CD, n = 112), #2: Inactive CD (n = 53), #3: Active ulcerative colitis (UC, n = 128), #4: Inactive UC (n =39), #5: IBS-Diarrhea predominant (n = 64), #6: Healthy Controls (HC, n = 52). The prevalence of positive stool tests was compared in patients with active inflammation (as defined by biomarkers) and those without. In active IBD patients, clinical characteristics, medication use, and disease course (need for escalation of steroids and surgeries) were compared between those with positive and negative tests. Results: Prevalence of infectious organisms was as follows: CD-active (33.9%), CD-inactive (3.8%), UC-active (28.9%), UC-inactive (12.8%), IBS-D (29.7%), HC (13.4%). Both CD-active and UC-active had significantly higher infection rates than inactive IBD or healthy controls. In addition, the prevalence of infectious agents was 9-fold higher in active vs. inactive CD (p = 0.0001) and 2-fold higher in active vs inactive UC (p = 0.04). Conclusions: Active CD and UC have a higher rate of detectable infectious agents than patients with quiescent disease, suggesting a significant number (>30%) of symptomatic IBD flares are due to intestinal infection. These appear to be mostly transient, and treatable with fluids and supportive care, allowing sparing of steroids.